1993
DOI: 10.1007/bf02599716
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating qualitative issues in residency training

Abstract: This study demonstrates the techniques needed to develop and use scaled program evaluation questionnaires. It is hoped that widespread use and validation of such instruments may result in greater responsiveness to the needs of trainees and more facilitative environments in which to acquire medical knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In line with the results of previous studies using the RQ on American samples [6, 7], our results showed high correlations of measures of depressive symptoms and emotional exhaustion with the RQ–Emotional Distress scale. The results also showed moderate and weak correlations of these measures with the RQ-Workload and RQ-Learning Environment Satisfaction scales.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the results of previous studies using the RQ on American samples [6, 7], our results showed high correlations of measures of depressive symptoms and emotional exhaustion with the RQ–Emotional Distress scale. The results also showed moderate and weak correlations of these measures with the RQ-Workload and RQ-Learning Environment Satisfaction scales.…”
Section: Discussionsupporting
confidence: 92%
“…Since its development in 1993 [7] and subsequent revision and validation in 1995 [6], the aspects measured by the RQ have been associated with mental health, education, and satisfaction of resident physicians and fellows from different programs in the United States [6, 811]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there was no perceived change in senior residents’ general wellbeing. Previous studies have reported mixed results in residents’ health, wellness and quality of life after implementation of night float systems [9,12,14,30] with some reporting such improvements as more time available to study, as well as negative consequences, such as increased depression and feelings of isolation [20-22,36]. …”
Section: Discussionmentioning
confidence: 99%
“…One approach is the night float rotation system, whereby residents provide patient care either during daytime shifts or during 12 to 16 hour overnight shifts [3,9,10,12,16]. Despite research showing the benefits of reduced consecutive duty hours and night float rotations, some contradictory evidence continues to emerge about the impact on residents’ wellness, ability to deliver health care and medical education experience [9,12,14,20-22]. Night float rotations can cause disruptions in basic biological functions, circadian rhythms, social relationships, and psycho-physical health [23].…”
Section: Introductionmentioning
confidence: 99%
“…A PACRE questionnaire was developed on the basis of existing literature [ 12 , 14 , 15 , 20 – 28 ]. Items were developed for each of the Stanford Faculty Development Program (SFDP) for Clinical Teaching categories: learning climate, control of session, communication of goals, promotion of understanding and retention, evaluation, feedback, and promotion of self-directed learning [ 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%